1993
DOI: 10.1093/bja/70.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Bupivacaine and Its Enantiomers During Continuous Extrapleural Intercostal Nerve Block

Abstract: Plasma concentrations of bupivacaine have been measured in 12 patients given bupivacaine through a paravertebral catheter placed under direct vision at thoracotomy. After an initial bolus of 0.5% bupivacaine 20 ml, mean (SEM) Cpmax was 1.45 (0.32) micrograms ml-1 and median (range) tCpmax was 25 (10-60) min. A concentration of 4.43 micrograms ml-1 measured in one patient was not associated with toxic signs. During continuous infusion of bupivacaine for 120 h, Cpmax was 4.9 (0.7) micrograms ml-1 and tCpmax 48 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Concentrations of local anesthetic usually employed in TPVB are low because of the risk of toxicity. Some reports suggest that it may be necessary to use higher concentrations to achieve better VAS scores [16,17]. However there are insufficient studies to determine if these higher concentrations of local anesthetic would provide better pain control without toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of local anesthetic usually employed in TPVB are low because of the risk of toxicity. Some reports suggest that it may be necessary to use higher concentrations to achieve better VAS scores [16,17]. However there are insufficient studies to determine if these higher concentrations of local anesthetic would provide better pain control without toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, perineural infiltration of intercostal nerves is associated with large and rapid absorption of local anaesthetic into the systemic circulation, leading to high blood concentration and potential toxic complications [2]. A plasma concentration of bupivacaine as high as 9.27 lg.ml , which exceeds the upper limit of safety for this drug, was reported by Berrisford and colleagues [3] after continuous paravertebral infusion of 0.5% bupivacaine at a rate of 5-10 ml.h )1 for 120 h.…”
mentioning
confidence: 99%
“…This underlines that the total dose of LAs administered should be a key issue in the planning of multimodal analgesia after thoracotomy surgery. To date, the pharmacokinetic parameters of bupivacaine administered as a continuous paravertebral infusion have not been studied in detail, but it has been shown that in some cases there may be toxic levels (2-4.5 mg/l) even in asymptomatic patients (15,16). This is due to the greater doses and volumes of LA required to reach a good level of analgesia at the paravertebral level compared to at the epidural level and, hence, the systemic absorption of LA (11).…”
Section: Discussionmentioning
confidence: 99%